Children Allergies in Saudi Arabia: The Situation and Challenges‒ Narrative Review - Tashkandi, Noha Farouk; Alonazi, Aishah Saud; Mahdi, Reham Hamoud; Muazen, Yaqeen Yahya; Al-Shilaly, Hamidah Ibrahim (International Journal of Child Health and Nutrition, 2025)
Pediatric allergic diseases like asthma, allergic rhinitis, eczema, and food allergies are highly prevalent in Saudi Arabia. This narrative review synthesizes diverse evidence on the prevalence, clinical presentation, and management of pediatric allergic diseases in Saudi Arabia, highlighting gaps in knowledge and practice to inform future healthcare strategies. Studies report allergy rates between 13-45% among Saudi children. Common medications used include antihistamines, nasal steroids, bronchodilators, and topical creams. While specific immunotherapy is growing in popularity for persistent IgE-mediated conditions. This paper reviews recent literature on the burden, management strategies, treatment options, and challenges regarding pediatric allergies in Saudi Arabia. Key challenges include a lack of awareness among families and even healthcare professionals, a shortage of pediatric allergy specialists, limited accessibility, high treatment costs, and a lack of standardized protocols. However, advancements in immunotherapy and oral food desensitization provide promising prospects. More research, public health initiatives, specialized workforce capacity building, improving affordability, and national guidelines will help address this major pediatric concern in the kingdom.